Curcumin delivery nanoparticles based on Maillard reaction of Haematococcus pluvialis protein/galactose for alleviating acute alcoholic liver damage - Xinyi Liu; Yukun Song; Shasha Cheng; Mingqian Tan (Food Science and Human Wellness)
The aim of this study is to investigate the feasibility of Maillard reaction products of Haematococcus pluvialis protein and galactose (HPP-GAL) for improving the bioactivities of curcumin (CUR) for alleviating alcoholic liver damage. CUR was embedded into HPP-GAL nanoparticles by the self-assembly of hydrogen bonding and hydrophobic interaction with the particle size around 200 nm. HPP-GAL enhanced the encapsulation efficiency and loading amount of CUR with the value of (89.21 ± 0.33)% and (0.500 ± 0.004)%, respectively. The stabilities of CUR under strong acid, salt ion stability and ultraviolet irradiation conditions were improved by the encapsulation. HPP-GAL-CUR nanoparticles exhibited excellent concentration-dependent in vitro antioxidant activities including DPPH and ABTS scavenging rates, and better protective effect on CUR against gastric acid environment as well as longer release of CUR in simulated intestinal fluid. In addition, the HPPGAL-CUR delivery system possessed liver targeting property due to the existence of GAL, which could effectively alleviate the alcohol-induced liver damage and the inflammation indexes by inhibiting the oxidative stress. Therefore, HPP-GAL-CUR nanoparticles might be a potential candidate system for the prevention of alcoholic liver damage in the future.